BTQ Teacher's Strategy in Overcoming Student Learning Difficulties at SMP Muhammadiyah 4 Gempol Pasuruan: Strategi Guru BTQ dalam Mengatasi Kesulitan Belajar Siswa di SMP Muhammadiyah 4 Gempol Pasuruan - Habibillah, Muhammad Hisyam; Astutik, Anita Puji (Journal of Islamic and Muhammadiyah Studies, 2024)
BTQ learning is directed to improve students' ability to read and write the Qur'an well, understand the content of the verses of the Qur'an, and be able to write it with good and correct writing. The function of learning to read and write the Qur'an (BTQ) functions, among others, is to develop the ability of students to read and write the Qur'an. Encourage, guide, foster willpower and passion. Embed understanding, understanding, appreciation and practice the content of the verses of the Qur'an in the behavior of students everyday. Providing knowledge to take education at a level that is more than one level. BTQ subjects at SMP Muhammadiyah 4 Gempol aim that students have the ability to read and write the Qur'an well, apply the rules of recitation in reading the Qur'an, memorize short letters in the Qur'an, write verses - verses of the Qur'an with good and correct writing. The aim is to encourage and encourage students or children easily, now they are more active in learning and understanding BTQ lessons. Highlights: Development of Quranic Literacy: Enhancing students' ability to read, write, and comprehend the Quranic text. Encouraging Active Learning: Fostering passion and engagement among students towards BTQ lessons. Integration into Daily Life: Embedding understanding and practice of Quranic verses in students' everyday behavior. Keywords: BTQ Teacher Strategy, Student Learning Difficulties, Qur'an Literacy